2018
DOI: 10.1007/s11239-018-1738-7
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction as a predictor of direct oral anticoagulant drug levels in atrial fibrillation patients

Abstract: Data are limited on the effects of drug interactions on direct-acting oral anticoagulant (DOAC) levels. We evaluated the effects of the use of interacting drugs on DOAC levels in patients with atrial fibrillation (AF). We reviewed data of AF patients tested for DOAC levels in 2013-2017. The primary outcomes were drug levels exceeding the expected steady-state range, and in the highest quartile. A multivariate analysis was performed to evaluate the correlation of treatment by the use of interacting drugs, CYP3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Our current findings support our previous study, which reported that the use of moderate CYP3A inhibitors was correlated with higher DOAC concentrations [38]. The concordance between the previous [38] and current data regarding the effect of enzyme inhibitors on DOAC concentrations may also validate the data used in the current analyses and our findings on the effect of EI-ASMs on DOAC concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Our current findings support our previous study, which reported that the use of moderate CYP3A inhibitors was correlated with higher DOAC concentrations [38]. The concordance between the previous [38] and current data regarding the effect of enzyme inhibitors on DOAC concentrations may also validate the data used in the current analyses and our findings on the effect of EI-ASMs on DOAC concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings showed that 611 (48.1%) of our patients were receiving at least one interacting medication with apixaban, which is consistent with previous studies that showed that the prevalence of drug interactions with DOACs ranges between (37–78%). 11 15 It is important to highlight that the prevalence of drug interactions with apixaban remains high and is consistent with other studies. One explanation of this high percentage could be due to polypharmacy in patients with atrial fibrillation.…”
Section: Discussionsupporting
confidence: 85%
“…Although fewer in number than warfarin [ 1 , 2 , 8 ], the clinical importance of pharmacokinetic DOAC DDIs is increased as the lack of an “INR-equivalent” results in less testing and monitoring – thus such interactions are likely to remain unnoticed until a complication occurs since DOAC levels are not routinely monitored. Currently, pharmacokinetic studies, case reports, and guidance documents based on these reports in the literature propose several pharmacokinetic DDIs for DOACs demonstrated by significant alterations in plasma DOAC concentrations [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ] but some occur in the absence of adverse clinical events [ [19] , [20] , [21] , [22] ]. While the ability of P-gp and/or CYP3A4 modifiers to alter DOAC drug levels is well-established, given the wider therapeutic index of the DOACs relative to a narrow therapeutic index drug like warfarin, it is unknown if these pharmacokinetic alterations are sufficient to contribute to clinical adverse events.…”
Section: Introductionmentioning
confidence: 99%